(untitled) (AYUSHDHARA, 2018)
Leucorrhoea (Shweta Pradara) is one of, the disease which is well known as Shweta Pradara in Ayurveda. So a more appropriate and effective treatment which is relatively quicker in action with more efficacy is the need of the hour. Ayurveda the science of human being have so many formulations to overcome Shwetapradara. Leucorrhoea disease, female genital system from introitus to uterus is described in Ayurveda as Tryavarta yoni, Rajovahastrotas which is Bahirmukhastrotas and due to this it is more prone to the exogenous infections. Gynecological problems are very common now-a-days. Among them Shwetapradara is one of the most observing disorders of women which occurs irrespective of socio-economic status, occupation, etc. It is caused by the vitiation of Kapha dosha. Though it is seen as a negligible factor initially, if not treated properly in time it will lead to major gynecological problems later. Shwetapradara can be correlated with leucorrhoea. Leucorrhoea, a common gynecological symptom troubles more than 75% of women during their life. One such formulation has been picked up in the present study. The main aim of the present study is to clinically evaluate the efficacy of Kukkutanda bhasma with Pushyanuga choorna and Yastimadhwadi sidda kashaya prakshalana in specific cases of Shwetapradara. Based on the subjective and objective parameters the criteria of assessment are set aside.